Hubungan antara Keharmonisan Keluarga dengan Harga Diri pada Remaja - Budianti, Ariska Karunia, Dr. Nanik Prihartanti, M.Si (2015)
The research aim to know the relationship between the family harmony with self-esteem on teenagers, knowing the level of family harmony in the teenagers, knowing the level of self-esteem on teenagers, and to know the contribution toward family harmony self-esteem on teenagers. The research choose quantitative methods to achieve the objectives of this research. The subject in this study are students class X SMA Muhammadiyah 1 Surakarta and consists of four grades X IPS 1, X IPS 2, X IPS 3, and X IPS 4. The results of the correlation coefficient (r) of 0,176 with p value = 0,018 < 0,05 which means there is a significant positive relationship between family harmony with self-esteem on teenagers. And from the results of the analysis found that the variable has the empirical average self-esteem (RE) 21,42 and of the average hypothetic of 17,5 which means the subject of self-esteem in this study belongs to high. Of variable harmonious family having an empirical average (RE) as much as 75,39 and hypothetic average (RH) as much as 57,5 which means harmonious family building in teenagers considered to be high. Effective contributions given harmonious family side variables to self-esteem to research to 0,31 which mean harmonious family building turn influences the amounting of teens 0,31% and there are 99,7 another factors.